Rumination and alexithymia serially mediate the relationship between mindfulness and anxiety symptoms in Chinese university students - Junchao Yuan; Luyu Chen; Hongye Geng (Scientific Reports)
Abstract Anxiety symptoms are highly prevalent among Chinese university students, significantly impairing psychosocial functioning. Although mindfulness has been identified as a protective psychological factor, the precise mechanisms underlying its association with anxiety symptom alleviation remain insufficiently understood. This study investigates the serial mediation effects of rumination and alexithymia in the relationship between mindfulness and anxiety symptoms. A cross-sectional study was conducted with 860 Chinese university students. Validated psychometric instruments were administered, including the Mindful Attention Awareness Scale (MAAS), Ruminative Response Scale (RRS), Toronto Alexithymia Scale (TAS-20), and Screen for Adult Anxiety Related Disorders (SCAARED). Serial mediation analyses were performed using SPSS 25.0 and Hayes’ PROCESS macro (Model 6), controlling for sex and academic grade. Higher mindfulness levels showed robust associations with lower anxiety symptom severity. This relationship was primarily linked to interconnected cognitive and affective pathways. The analysis revealed that individuals reporting higher mindfulness exhibited lower tendencies toward repetitive negative thinking (rumination), which corresponded to lower anxiety levels. Simultaneously, higher mindfulness was associated with lower alexithymia that typically co-occur with anxiety symptoms. Crucially, a sequential pathway emerged: higher mindfulness correlated with lower rumination, which in turn corresponded to fewer emotional processing difficulties (alexithymia), ultimately associating with fewer anxiety symptoms. Collectively, these indirect pathways accounted for most of mindfulness’s observed relationship with anxiety symptoms, highlighting interconnected roles of cognitive and emotional factors. Mindfulness shows protective associations with anxiety symptoms through dual correlations: correspondence with lower rumination and relationship with lower alexithymia. These findings advocate for interventions addressing both cognitive patterns and emotional regulation in culturally adapted campus mental health programs.